The Immunity of the Administration of State Financial Policy and Financial Stability System in Emergency - I Made Suwarjana (Yuridika, 2022)
Officials involving in the prevention and mitigation of corona virus want to be given the right of immunity or legal immunity in implementing discretion authority as a guarantee and legal certainty that any decided policy will not be tested or used as the basis for bringing criminal action. The formation of Government Regulation in Lieu of Law (Perpu) No.1 Year 2020, which is aimed to handle the corona virus pandemic (COVID-19) actually comes with noble purpose. But the authorization of immunity right or legal immunity to the officials might cause state financial loss and tend to generate abuse of power.  This study aims to study the concept of state financial loss, its accountability and legal immunity on criminal responsibility over the state financial loss as the impact of decision-making by officials in handling Covid-19. This was a legal research type that applies statute approach, conceptual approach, comparative approach, and case approach. Legal immunity is a form of legal protection for parties carrying out tasks and responsibilities under a good faith.